Social Boycott - Cruz, Breno de Paula Andrade (Review of Business Management, 2017)
Purpose – Based on Corporate Social Responsibility (CSR) aspects, Social Boycott is presented in this paper as an amplification of the Labor Boycott concept. Design/methodology/approach – A statistical experiment with 240 individuals has been carried out, so that it could verify if consumers’ perceptions related to the Management Context of Corporate Social Responsibility (MCCSR) of the fictitious Alpha company has considerable impact on the variable Boycott Efficacy (BE), and on the Boycott Intention (BI). The ANOVA has been used to show causeeffect variable relationship. Findings – MCCSR impacts on BE (H1) and BI (H2). Thus, the Social Consumer’s boycott motivation is driven by the perception of the level of CSR management orientation a company has (anti-corruption internal measures, organizational climate, labor conditions and waste management during production process). While Labor Boycott restricts its analysis to labor conditions, the concept of Social Boycott incorporates all CSR aspects. Originality/value – This study presents Social Boycott definition and its insertion on consumer boycott literature - types of boycott and boycott motivations (ideological dimension). Thus, tangential analysis such as experiential dimension and a theoretical political boycott gap are discussed.